Nickel-Catalyzed Reduction of Secondary and Tertiary Amides - Simmons, Bryan J. (Org Lett, 2017)
The nickel-catalyzed reduction of secondary and tertiary amides to give amine products is reported. The transformation is tolerant of extensive variation with respect to the amide substrate, proceeds in the presence of esters and epimerizable stereocenters, and can be used to achieve the reduction of lactams. Moreover, this methodology provides a simple tactic for accessing medicinally relevant α-deuterated amines.